Successful laparoscopic management of diaphragmatic pregnancy:a rare case report and brief review of literature - Lifeng Chen; Jinwei Liu; Jing Shu; Wenjie Zeng; Xiaofeng Zhao (BMC, 2019)
Abstract Background Abdominal ectopic pregnancies are rare category of ectopic pregnancies.We describe a ectopic pregnancy implanted on the surface of diaphragm and highlight the difficult clinical course of an abdominal ectopic pregnancy managed with strategic procedural intervention. Case presentation A 33-year-old Chinese woman with abdominal pain was diagnosed with ectopic pregnancy implanted in the liver according to CT and advised to transfer the patient to tertiary referral center. The patient had a significant increasing abdominal pain and intense reflex sensitivity in the right shoulder when she presented to our hospital. Laparoscopic surgery was decided immediately with the impression of ruptured abdominal pregnancy and hemorrhagic shock. It was found that ectopic pregnancy was implanted on the diaphragmatic surface.The pregnant tissue was completely resected from the diaphragm and bipolar electrocoagulation was used to control bleeding. The patient was stable and discharged 3 days after surgery in a good condition. Conclusion CT or MRI should be considered as an alternative to TVS in the management of ectopic pregnancy patients with unusual presentations. A thorough observation of the entire pelvis and upper abdomen during laparoscopic exploration is crucial for diagnosis.